Process optimization of vacuum fried mango (Mangifera indica L. cv. Carabao) using response surface methodology - Mariano, Christine Bernadette d.G
This study aimed to optimize the process parameters of the vacuum frying of Carabao mango chips using the response surface methodology (RSM). Specifically, the study 1) evaluated the effects of stage ripeness and process parameters (vacuum frying time , vacuum frying temperature, and loading capacity) on the equality of vacuum fried mango (Mangifera indica L. cv. Carabao) chips; and, 2) established and validated the optimized process parameters for the vacuum frying of the mango (Mangifera indica L. cv. Carabao) chips Carabao mangoes at day 7 after harvest (120 days after flower induction (DAFI) + 7 days after harvest) produced vacuum fried Carabao mango chips with the highest overall acceptability rating (7.07 "like moderately"). Statistical models were generated to predict the effects of process parameters on the color (L*, a*, b*) values, moisture content (% dry basis), water activity, yield (%), and sensory properties (appearance, color, aroma, texture, flavor, and overall acceptability) on the quality of vacuum fried Carabao mango chips. All models, except for water activity, were considered significant (p<0.05). The optimal combination of the process parameters that would result to vacuum fried Carabao mango chips with desirability index of 0.797, were: 60 s frying time, 93 celsius frying temperature, and 3.38 kg loading capacity. Validation of the optimized vacuum frying process parameters (time, temperature, and loading capacity) showed that both optimal and non-optimal vacuum fried Carabao mango chips, fall within their respective % confidence (CI) and prediction intervals (PI) at significant level of α=0.05.